2018
DOI: 10.1158/1538-7445.am2018-4769
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 4769: Identification of differentially expressed microRNAs in African American women with quadruple-negative breast cancer

Abstract: Purpose: Recently, we have demonstrated that triple-negative breast tumors (TNBC) that lack the expression of androgen receptor are quadruple-negative tumors (QNBC) and have increased aggressiveness. Additionally, we determined that this is due to a unique gene signature in the QNBC subtype. However, whether this gene signature is associated with a unique miRNA expression and differential in African American (AA) women compared to Caucasian (CA) women has not been determined. Therefore, the purpose of this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…MiR-135b expression was strongly and positively correlated with a high proliferative index. A recent study of African American women with QNBC by Angajala et al identified differentially expressed miRNAs associated with the disease [ 59 ]. This study compared TCGA miRNA sequencing results from women with QNBC, AR+ TNBC, luminal and Her2+ breast cancers.…”
Section: Dysregulated Mirnas Related To Qnbc and Their Molecular Func...mentioning
confidence: 99%
See 1 more Smart Citation
“…MiR-135b expression was strongly and positively correlated with a high proliferative index. A recent study of African American women with QNBC by Angajala et al identified differentially expressed miRNAs associated with the disease [ 59 ]. This study compared TCGA miRNA sequencing results from women with QNBC, AR+ TNBC, luminal and Her2+ breast cancers.…”
Section: Dysregulated Mirnas Related To Qnbc and Their Molecular Func...mentioning
confidence: 99%
“…In analysis of the few published studies that identify differentially regulated miRNAs in QNBC versus AR+TNBC, regulation of PI3K/PTEN and Myc signaling, superoxide dismutase and cell-cycle checkpoint come into view as potential pathobiologically meaningful pathways that may be dysregulated by disease-specific miRNAs. The analysis of TNBC subtypes in African American women by Angajala et al identified differentially regulated miRNAs that regulate Myc, TP53 and PTEN [ 59 ]. The use or targeting of these miRNAs and targets may have promise as therapeutic approaches, and PI3K/Akt/mTOR and cell cycle regulators have been previously considered to be prospective therapies for QNBC [ 15 ].…”
Section: Translational and Clinical Implications Of Known Dysregulate...mentioning
confidence: 99%
“… 27 Significant differences in QNBC biology between WA and CA women have also been reported. For instance, Angajala et al 93 reported a lower expression of hsa-mir-190b among AA patients with QNBC. There are limited data on QNBC in WA as AR expression analysis is uncommon.…”
Section: Prevalence Of Quadruple-negative Breast Cancer In West Africamentioning
confidence: 99%